Elementary approach to the Hartogs extension theorem - Simonič, Aleksander (Matrika, 2016)
In this paper we present a proof of Hartogs' extension theorem, following T. Sobieszek's paper from 2003. Hartogs' theorem provides a large class of domains where holomorphic functions have analytic continuation to larger domains, and is "a several complex variables theorem" in nature because its conclusion is false in the complex plane. Sobieszek's proof is quite remarkable because he uses, stated in his paper without proofs, only higher-dimensional identity principle for holomorphic functions and Cauchy's integral formula for compact sets. We proved this two theorems here, making this exposition self-contained. The only background required is an undergraduate course in real and complex analysis and in point-set topology.
Keywords: complex analysis; function theory; funkcijska teorija; Hartogs extension theorem; Hartogsov razširitveni izrek; kompleksna analiza; matematika; mathematics